Effect of primary dietary sources and environmental variables on the condition of freshwater pearl mussel (Margaritifera margaritifera) populations - Nykänen, Sabrina (2021)
Earlier studies have suggested effect of land use on freshwater pearl mussel (FPM) via the detrimental impact of siltation on juvenile mussels, but little is known about its effects through the changes in food quality. Moreover, the relative role of autochthonous and allochthonous food source of FPM is largely unstudied. Therefore, the aim of this study was to investigate relationship between food source and performance of adult FPM, with the hypothesis that condition of mussels would correlate positively with the availability of autochthonous food. The mean shell opening resistance (SOR) and FPM density were used as indicators of the condition of the populations in 14 northern Finnish rivers. The diet of FPM was studied by analyzing stable isotope ratios (δ13C, δ15N, and δ2H) of the mussel foot tissue and the potential food sources. The contribution of autochthonous and allochthonous sources in the diet of FPM and its connection to the condition of the populations were examined with Bayesian mixing models. There was markable variation in the autochthonous source signal between the rivers, which may possibly be explained with the higher terrestrial organic matter contribution in the lake fine particulate organic matter in southern rivers. Mixing model medians suggested overall dominance of autochthonous sources in diet of FPM. Mixing model with mean SOR as a continuous effect explained best the variation in FPM diet, so that there was surprisingly a tendency of allochthonous contribution to increase with SOR, suggesting a possible positive association between condition of FPM and the proportion of allochthonous sources in the diet. Further studies are still needed to understand the relationship between food sources and condition of FPM, and the possible effect of land use on FPM via changes on food quality, but the present study suggests that although autochthonous sources largely dominate, the allochthonous food sources in diet of FPM can be of high importance for the performance of the individuals.